Phytoremediation of Iron and Antimony Polluted Waste Dump Sites in Anyigba Kogi State, Nigeria: A Multivariate Statistical Technique - Ameh, E.G. (Global Journal of Earth Science and Engineering, 2023)
Soil degradation by anthropogenic means is increasing day after day all over the globe, particularly in Nigeria. This research became necessary to show how plants grown surrounding waste dumps are able to mitigate soil pollution by Fe and Sb. Both media (plants and soils) were collected, and leached, and analyses were performed to assess the quantum of Iron and Antimony found within sampled media. The EDX3600B X-ray fluorescence spectrometer was used to analyze for soil and plants sampled. The bioconcentration factor (BCF), translocation factor (TF), bioaccumulation coefficient (BAC), and metal uptake efficacy (%) ME for both media were calculated. The evaluated data revealed that Colocasia esculent and Amaranthus viridis showed the maximum capacity as Fe hyperaccumulators. Also, Colocasia asculenta, Physalis angulate, and Zea mays were suitable plants as hyperaccumulators of Sb. Only Loportea aestuans suffices as phytoextractor for Antimony. Amaranthus hybridus, Colocasia asculenta, and Corchorus aestuans have capacities to stabilize Sb in soils. Species collected showed the required ability as phytominers of Sb. The quantities of Iron and Antimony in acquired media were higher than allowable benchmarks in leaves (vegetables). From this investigation, the acquired plants showed evidence of good specimens with abilities to remove Iron and Antimony from the soil. The collected species also showed attributes and characteristics of good reservoirs of Iron and Antimony.